Performance Analysis Of Malaysian Low Voltage Distribution Network Under Different Solar Variability Days - Zolkifri, Nur Izzati; Gan, Chin Kim; Shamsiri, Meysam (Institute of Advanced Engineering and Science, 2019)
The widespread of Photovoltaic (PV) systems as one of the distributed generation technologies could have profound impact on the distribution networks operation, particularly on network losses and network voltages fluctuations. This is mainly caused by the high PV penetrations coupled with high solar variability in the countries with large cloud cover. Therefore, this paper presents an investigation on the impact of residential grid-connected PV system by utilizing a typical low voltage (LV) network in Malaysia under various solar variability days. In this study, there are three scenarios; where, each scenario were performed with different levels of PV penetration and five different solar variability days. The impacts of PV system allocation in different scenarios and various solar variability days are assessed in term of voltage unbalance and network losses. The results propose that Scenario 1: randomly allocation of PV systems across the LV network has the lowest voltage unbalance and network losses especially during overcast day.